The Effect of Capital Structure, Working Capital Turnover and Firm Size on Firm Value in Property and Real Estate Sector Companies Listed on Indonesia Stock Exchange - Shintya Rinaldy; Lintje Kalangi; Meily Yoke Betsy Kalalo (Jurnal Ekonomi dan Bisnis Digital, 2023)
The purpose of this research is to determine the effect of capital structure, working capital turnover, and firm size on firm value in the property and real estate sectors listed on the Indonesia Stock Exchange for the 2018–2021 periods. This study uses a quantitative method with purposive sampling as a method of selecting samples, and 30 companies were chosen as samples. There are 120 observations obtained in this observation. The data analysis is multiple linear regressions with IBM SPSS 25 as the data processor. The results show that capital structure had a positive but not significant effect on firm value, working capital turnover had a positive effect on firm value, and firm size hurt firm value.